2018
DOI: 10.1002/jcp.26442
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic miR‐125b inhibits insulin signaling pathway by targeting PIK3CD

Abstract: Insulin resistance is often characterized as the most critical factor contributing to the development of (T2D) type 2 diabetes. MicroRNAs (miRNAs) are endogenous non-coding short single-stranded RNAs that function as negative regulators in many physiological and pathological processes. The objective of this study was to evaluate the roles of miR-125b in the regulation of insulin sensitivity in hepatocytes. We found that hepatic miR-125b levels were significantly increased in the patients with type 2 diabetes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 42 publications
0
22
1
Order By: Relevance
“…Here, we revealed circulating miRNA profiles of MetS patients via microarray analysis and confirmed that circulating miR-143-3p was increased significantly in MetS patients compared with controls, both in serum and urine samples. Recently, Rui Wang et al reported that elevated circulating miRNA-122 is associated with obesity and insulin resistance in young adults, 19 Xiliang Du et al revealed that miR-125b overexpression impaired the insulin signaling pathway in HepG2 cells, L02c cells, and primary hepatocytes, 20 while, He Qing Fang et al showed that circulating miRNA-21 is downregulated in patients with MetS. 21 However, neither of these 2 miRNAs was detected in our present study.…”
Section: Discussioncontrasting
confidence: 58%
“…Here, we revealed circulating miRNA profiles of MetS patients via microarray analysis and confirmed that circulating miR-143-3p was increased significantly in MetS patients compared with controls, both in serum and urine samples. Recently, Rui Wang et al reported that elevated circulating miRNA-122 is associated with obesity and insulin resistance in young adults, 19 Xiliang Du et al revealed that miR-125b overexpression impaired the insulin signaling pathway in HepG2 cells, L02c cells, and primary hepatocytes, 20 while, He Qing Fang et al showed that circulating miRNA-21 is downregulated in patients with MetS. 21 However, neither of these 2 miRNAs was detected in our present study.…”
Section: Discussioncontrasting
confidence: 58%
“…Thus, miRNAs is very likely to be the link between gut microbiota and NAFLD. The miRNAs we scanned were stably expressed in the liver and involved in the course of NAFLD such as hepatic steatosis (miR10b [ 60 ], miR-24 [ 61 ], miR-29a [ 62 ], miR-155 [ 63 ], miR-34a [ 64 ], miR-125b [ 65 ], miR-486 [ 66 ], miR-199a [ 67 ], miR-30b [ 68 ], miR-30c [ 69 ], miR467b [ 70 ], miR-148a [ 71 ]), insulin resistance (miR-125b [ 72 ], miR-206 [ 73 ], miR-130a [ 74 ], miR-291b [ 75 ]), inflammatory and hepatic fibrosis (miR-21a [ 76 , 77 ], miR-199a [ 78 ], miR-370 [ 79 ], miR-130a [ 80 ], miR-34a [ 81 ], miR-24 [ 82 ]), as well as cirrhosis and HCC (miR-210 [ 83 ], miR-10b [ 84 ]). We further analyzed the correlation between the alteration of gut microbiota and miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of glucose and insulin were measured using biochemical (U83730050, Guilin Unitech Medical Electronics Co., Ltd., Guilin, China) and ultra-sensitive mouse insulin immunoassay kit (Li Ka Shing Faculty of Medicine, The University of Hong Kong) according to the supplier's protocol, respectively. Homeostasis model assessment of insulin resistance (HOMA-IR) index was calculated according to the formula: [fasting glucose level (mM)] × [fasting serum insulin (mU/L)]/ 22.5 (Du et al, 2018).…”
Section: Serum and Liver Biochemical Analysismentioning
confidence: 99%